Design and development of test rig for PIV fluid flow experiment for biomedical engineering application - Mohd Jamil Mohamed, Mokhtarudin; Mohamad Fairul, Hubakri; Mohd Amirul Syafiq, Zamri; Mohd Noor Akmal, Hamzah; Rabiatul Adawiyah, Roslan (2021)
Particle Image Velocimetry (PIV) is the process of using a laser in conjunction with a camera to measure particle velocities. PIV is usually used to study the flow dynamics of wind in a tunnel and fluid in a complex structure. Therefore, the specialized test rig for PIV has to be made for specific cases to be studied. The test rig is mainly concentrated on the design and development of a test rig for a PIV experiment for the investigation of blood flow dynamics in a blood vessel, which must be able to allow the laser to pass through and shine on the fluid and the seeding particles. Hence, a test rig contains the connection between artificial blood vessels and the fluid flow pump with adjustable position of inlet and outlet is developed. PIV setup is equipped with laser and stand, camera and seeding particles in CARIFF, UMP Gambang.